In Vitro and In Vivo Efficacies of T-3811ME (BMS-284756) against Mycoplasma pneumoniae - Takahata, Masahiro (American Society for Microbiology, 2001)
T-3811, the free base of T-3811ME (BMS-284756), a new des-F(6)-quinolone, showed a potent in vitro activity (MIC at which 90% of the isolates tested are inhibited [MIC(90)], 0.0313 μg/ml) against Mycoplasma pneumoniae. The MIC(90) of T-3811 was 4-fold higher than that of clarithromycin but was 4- to 8-fold lower than those of trovafloxacin, gatifloxacin, gemifloxacin, and moxifloxacin and was 16- to 32-fold lower than those of levofloxacin, ciprofloxacin, and minocycline. In an experimental M. pneumoniae pneumonia model in hamsters, after the administration of T-3811ME (20 mg/kg of body weight as T-3811, once daily, orally) for 5 days, the reduction of viable cells of M. pneumoniae in bronchoalveolar lavage fluid was greater than those of trovafloxacin, levofloxacin, and clarithromycin (20 and 40 mg/kg, orally) (P < 0.05).